2010
DOI: 10.1007/s12032-010-9652-7
|View full text |Cite
|
Sign up to set email alerts
|

Slug regulates proliferation and invasiveness of esophageal adenocarcinoma cells in vitro and in vivo

Abstract: Slug is a transcription factor and E-cadherin repressor, which has recently been demonstrated to be important for cancer cells to down-regulate epithelial markers and up-regulate mesenchymal markers in order to become motile and invasive. In the present study, we assessed the relevance of Slug for invasion and growth potential of esophageal adenocarcinoma (EA) cells in vitro and in vivo. Slug expression was detected in nine human esophageal cancer cell lines. OE33 cell line was infected with Slug siRNA to knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 20 publications
4
28
0
Order By: Relevance
“…Expression of SLUG has been found to be elevated in tumour metastasis in various types of tumours (Zhang et al 2010). In an experiment conducted on a breast cancer mouse model, it was found that SLUG promotes metastasis by partially inhibiting E-cadherin (Casas et al 2011).…”
Section: Slugmentioning
confidence: 99%
“…Expression of SLUG has been found to be elevated in tumour metastasis in various types of tumours (Zhang et al 2010). In an experiment conducted on a breast cancer mouse model, it was found that SLUG promotes metastasis by partially inhibiting E-cadherin (Casas et al 2011).…”
Section: Slugmentioning
confidence: 99%
“…SiRNA transfections T24 cells at 70% confluence were stably transfected either a control vector (pDC316-EGFP-U6, mock) or Slug siRNA expressing pDC316-EGFP-U6 vector (Slug siRNA) (kindly provided by Dr. Zhang K, General surgery, the Affiliated Hospital of medical college, QingDao University, China) using Lipofectamine2000 Ò (Invitrogen) [8].…”
Section: Cell Line and Animalsmentioning
confidence: 99%
“…The product was subcloned into the expression vector pGEM-T and the pDC316-EGFP-U6 to construct the pMMP-2 cDNA or pEGFP expression plasmid as previous methods described [8]. Slug siRNAtransfected T24 cells were transiently transfected pMMP-2 cDNA for 48 h according to the manufacturer's instruction.…”
Section: Mmp-2 Cdna Plasmid Construction and Transfectionmentioning
confidence: 99%
See 2 more Smart Citations